Low drug levels and thrombotic complications in high‐risk atrial fibrillation patients treated with direct oral anticoagulants. (17th April 2018) - Testa, S.; Paoletti, O.; Legnani, C.; Dellanoce, C.; Antonucci, E.; Cosmi, B.; Pengo, V.; Poli, D.; Morandini, R.; Testa, R.; Tripodi, A.; Palareti, G.
Abstract : Essentials Direct oral anticoagulants (DOACs) do not require laboratory monitoring currently. DOAC specific measurements were performed at trough in patients with atrial fibrillation. Patients who developed thromboembolic events showed lower DOAC plasma levels. This study supports the concept of measuring DOAC levels at steady state. Summary: Background: Direct oral anticoagulants (DOACs) are administered at fixed doses without the need for dose adjustment according to laboratory testing. High interindividual variability in drug blood levels has been shown with all DOACs. To evaluate a possible relationship between DOAC C‐trough anticoagulant levels and thromboembolic events, 565 consecutive naive patients with atrial fibrillation (AF) were enrolled in this study performed within the START Laboratory Registry. Methods: DOAC‐specific measurements (diluted thrombin time or anti‐activated factor II calibrated for dabigatran; anti‐activated FX calibrated for rivaroxaban or apixaban) at C‐trough were performed locally at steady state within 15–25 days after the start of treatment. For each DOAC, the interval of C‐trough levels, from the limit of quantification to the highest value, was subdivided into four equal classes, and results were attributed to these classes; the median values of results were also calculated. Thromboembolic complications occurring during 1 year of follow‐up were recorded. Results: Thromboembolic events (1.8%) occurred in 10 patients who had baseline C‐trough levels in the lowest class of drug levels. The incidence of thromboembolic events among patients with DOAC C‐trough levels in the lowest level class was 2.4%, and that in the remaining groups was 0%. The patients with thrombotic complications also had a higher mean CHA2 DS2 ‐VASc score than that of the total patient population: 5.3 (95% confidence interval [CI] 4.3–6.3 versus 3.0 (95% CI 2.9–3.1). Conclusion: In this study cohort, thrombotic complications occurred only in DOAC‐treated AF patients who had very low C‐trough levels, with a relatively high CHA2 DS2 ‐VASc score. Larger studies are warranted to confirm these preliminary observations.